Applied numerical methods using MATLAB® - Yang, Wŏn-yŏng, 1953-; Cao, Wenwu; Kim, Jaekwon, 1972-; Park, Kyung W., 1976-; Park, Ho Hyun, 1964-; Joung, Jingon, 1974-; Ro, Jong Suk, 1975-; Lee, Han L., 1983-; Hong, Cheol Ho, 1977-; Im, Taeho, 1979- (John Wiley & Sons, Inc., 2020)
"This book makes use of MATLAB software to teach the fundamental concepts using the software to solve practical engineering and/or science problems. The programs are presented in a complete form so that readers can run them instantly with no programming skill, allowing them to focus on understanding the mathematical manipulation process and making interpretations of the results. The book targets students who do not like and/or do not have time to derive and prove mathematical results, helping them develop their problem-solving capability without being involved in details about the MATLAB codes. It also targets students who want to delve into details, helping them understand underlying algorithms and equations as deeply as they want"--